Інноваційний потенціал молоді: проблеми реалізації на ринку праці - Красножон, Н.С. (Стратегія і механізми регулювання промислового розвитку, 2013)
Висвітлено новітні тенденції та регіональні особливості функціонування молодіжного середовища, виявлено основні проблеми реалізації інноваційного потенціалу молоді на ринку праці України. Запропоновано пріоритетні напрями розвитку та регулювання молодіжного сегмента у структурі національного ринку праці. Освещены новейшие тенденции и региональные особенности функционирования молодежной среды, выявлены основные проблемы реализации инновационного потенциала молодежи на рынке труда Украины. Предложены приоритетные направления развития и регулирования молодежного сегмента в структуре национального рынка труда. Because of the lack of the effective regulatory mechanisms in the functioning of the labor market the employment potential of the population is not used effectively and efficiently today, not fully directed at achieving the objectives of innovation and economic growth. The lack of progressive structural changes in the economy and, consequently, in employment, braking innovative transformations, prevents the formation of sustainable innovative segments of the labor market, particularly the youth, since it enhances the competitiveness of the workforce, providing progressive economic development. The socio-economic potential of the country now and in the future depends on the youth labor activity, and the participation of youth in the economic activity is a significant factor in the socio-cultural and professional development. The market economy, on the one hand, greatly expanded the limits of application of forces and capabilities of young people at work, on the other - has led to a weakening of the state support for young people in social and labor issues, has shaken the foundations of the old institutional socialization of youth employment. Considering the specific “youth segment” of the national and regional labor markets, it should be noted that it is characterized by a sustainable growth in labor supply. This is due to the annual growth of the labor market of graduates at various levels. The problems of balancing supply and demand in this segment are explained by three reasons: first, the competition under which other age groups due to their professionalism and experience have less risk of losing their jobs and have more advantages in employment, and secondly, the lack of demand for a particular profession, forcing the young people to retrain and not work in the specialty, and thirdly, the constant change in life priorities caused by unjustified expectations of the maintenance, the conditions of work, the resulting income. Among the listed causes of low labor activity of young people are: employment opportunities for youth are limited, particularly for the individuals with special education and training and for those who do not have work experience, wages tend to be lower than for other age groups of workers and working conditions - worse than for more experienced people. Because of this, and ineffective government policies to promote employment of young people of the youngest age group they often prefer to delay the entry into the labor market, continuing education, giving birth to a child and being on leave to care for children, or to do nothing officially. Priority measures to improve the regulation of the youth segment, particularly in the development of its innovative component, the labor market can be defined as follows: 1) intensification of the urban community (civic, charitable and religious organizations) in support of social programs, projects and activities to enhance the capacity of young people; 2) reservation of jobs in enterprises, institutions, organizations, cities for youth employment, which give the first job; 3) competitive activities of business plans of young entrepreneurs and students of higher educational institutions, improvement of the mechanism of their realization and the implementation of the best projects in the region's economy; 4) continuous state coverage of the implementation of youth policy in the media to provide a new level of awareness and knowledge of young professionals in the region of vitally important issues.